Some Implications for Monetary Policy of Uncertain Exchange Rate Pass-Through - Hunt, Benjamin (IMF Working Papers; Working Paper ;, 2003)
The paper uses MULTIMOD to examine the implications of uncertain exchange rate pass-through for the conduct of monetary policy. From the policymaker's perspective, uncertainty about exchange rate pass-through implies uncertainty about policy multipliers and the impact of state variables on stabilization objectives. When faced with uncertainty about the strength of exchange rate pass-through, policymakers will make less costly errors by overestimating the strength of pass-through rather than underestimating it. The analysis suggests that pass-through uncertainty of the magnitude considered does not result in efficient policy response coefficients that are smaller than those under certainty.